Pengaruh Model Project-Based Learning Terhadap Perkembangan Sosial Emosional Anak Usia Dini Di Paud Dahlia - Nurhalisa, Mitha; Hidayat, Yusuf; Purbayani, Rini (Sekolah Tinggi Ilmu Agama Islam Putra Galuh Ciamis, 2024)
This study aims to analyze children's social-emotional development before and after implementing the Project-Based Learning model and to examine its effect on children aged 4-5 years at PAUD Dahlia, Cikoneng District. The research employed a pre-experimental method with a One-Group Pre-test Post-test design. The subjects were 15 children selected using a saturated sampling technique. Data were collected through observation and analyzed using the N-Gain and Wilcoxon tests with the help of Excel 2010 and SPSS 22. The pre-test results indicated that 87% of the children were in the Not Yet Developed (NYD) category, and 13% were in the Starting to Develop (SD) category. After implementation, post-test results showed improvement, with 40% of children in the Developing as Expected (DAE) category and 60% in the Very Well Developed (VWD) category. The Wilcoxon test indicated a significance value of 0.001, suggesting that the model significantly improves children’s social-emotional development. Thus, Project-Based Learning is proven effective for early childhood education.